Case Report: Chinese female patients with a heterozygous pathogenic RPS6KA3 gene variant c.898C>T and distal 22q11.2 microdeletion - Cong, Yan; Jin, Hongxing; Wu, Ke; Wang, Hao; Wang, Dong (Frontiers in Genetics, 2022)
Background: Coffin-Lowry syndrome (CLS) [OMIM#303600] is a rare X-linked dominant syndrome, caused by highly heterogeneous loss-of-function mutations in the RPS6KA3 (OMIM*300075) gene, and characterized by intellectual disability, short stature, tapered fifingers, characteristic facial features and progressive skeletal changes. We investigated the genetic etiology of a Chinese pedigree with intellectual disability (ID), short stature, digit abnormalities, facial dysmorphism, menstrual disorder and . using trio-based whole-exome sequencing (trio-WES). To our knowledge, female Chinese patients with c.898C>T (p.R300X) had not been reported detailedly in literature. The aim of this study was to provide clinical characteristics of these Chinese female CLS patients, which could be comparable to what has been described in other ethnicities. Case presentation: We described a Chinese family with three affected females, the mother (47 years old), the elder sister (21 years old) and the proband (17 years old). The mother and the elder sister had more severe clinical phenotypes than the proband. The common characteristics of them were intellectual disability (ID), short stature, facial dysmorphism, irregular menstruation and cardiovascular disorders.Trio-WES identified a heterozygous nonsense RPS6KA3 gene variant c.898C>T(p.R300X). Sanger sequencing verified variants of this family. The results of low-coverage massively parallel copy number variation sequencing (CNV-seq) showed that both the mother and the elder sister carried a CNV seq. The analysis of qPCR data demonstrated that the relative quantification of mRNA expressed by mutational RPS6KA3 gene in blood samples of the mother and the elder sister was significantly lower than normal female blood samples, but which of the proband was significantly higher. X-chromosome inactivation(XCI) study demonstrated that the elder sister showed extremely skewing in XCI and the XCI pattern of the proband was random. Conclusions: we herein reported, three female patients from China, which were identified a RPS6KA3 gene variant c.898C>T(p.R300X) by trio-WES. To our knowledge, Chinese patients with this variant had not been reported previously in literature. The three female patients presented with variable degrees of severity, which expanded phenotypic spectrum. The aim of this study was to provide clinical characteristics of these Chinese female CLS patients, which could be comparable to what has been described in other ethnicities.